Before & after a whole house of faux painting demonstrations! (Faux Fun, 2004)
Demonstrates a number of textured finishes for interior walls. Techniques covered in program: crosshatching; water stain glazing; antique glazing; abstract brushing; distressed paint finish; fan texture; antique texturing; Picasso sponge; glazing with angel prints.